Improvement of 4 K cooling power by coaxial pipe regenerator for a Gifford-McMahon cryocooler. Issue 1 (April 2021) - Masuyama, S; Matsumoto, K; Numazawa, T
Abstract: This paper presents the experimental results of 4.2 K cooling power of a Gifford-McMahon (G-M) cryocooler. To improve the cooling power, an original regenerator structure named coaxial pipe regenerator was applied to the second stage regenerator. This structure is that a stainless steel pipe is inserted in the coaxial direction of the second stage regenerator. An effect of the coaxial pipe is considered to rectify the helium flow in the regenerator that leads to an increase in the mass flow rate to the expansion space. Then, an improvement in the cooling power is expected. The second stage regenerator is comprised of three-layer of Pb (warm side), HoCu2 (middle) and Gd2 O2 S (cold side) spheres of which the volume filling rate is 50, 20 and 30%, respectively. The coaxial pipe is applied to each material layer independently to survey an improvement effect of the cooling power at 4.2 K. These coaxial pipe regenerators were tested with a G-M cryocooler of one-watt model (RDK-408D2, SHI) and a scroll-type compressor (SSC-3700, SUZUKISHOKAN). The three-layer regenerator (without coaxial pipe) obtained the cooling power of 1.70 W. When the coaxial pipe was applied to the Pb layer, the cooling power of 1.79 W was achieved with the electrical input of compressor of 7.06 kW. In contrast, the coaxial pipe of HoCu2 layer and Gd2 O2 S layer showed no conspicuous improvement. These results prove that the flow condition of helium in the Pb layer significantly affects the 4 K cooling power.